Church, state, and family reconciling traditional teachings and modern liberties - Witte, John 1959- (Cambridge University Press, 2019)
This book defends the fundamental place of the marital family in modern liberal societies. While applauding modern sexual freedoms, John Witte, Jr also defends the traditional Western teaching that the marital family is an essential cradle of conscience, chrysalis of care, and cornerstone of ordered liberty. He thus urges churches, states, and other social institutions to protect and promote the marital family. He encourages reticent churches to embrace the rights of women and children, as Christians have long taught, and encourages modern states to promote responsible sexual freedom and family relations, as liberals have long said. He counsels modern churches and states to share in family law governance, and to resist recent efforts to privatize, abolish, or radically expand the marital family sphere. Witte also invites fellow citizens to end their bitter battles over same-sex marriage and tend to the vast family field that urgently needs concerted attention and action
Keywords: Geschichte; Eherecht; Christentum; Staat; Eheschließung; Ehe; Familie; Families / Religious aspects / Christianity / History of doctrines; Marriage / Religious aspects / Christianity / History of doctrines; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books